Предмет: Алгебра,
автор: Рася666
Решите уравнение:(y-1)-(y-2)(y+2)=y-4
Ответы
Автор ответа:
0
(у - 1) - (у - 2)(у + 2) = у - 4
у - 1 - (у² - 4) = у - 4
у - 1 - у² + 4 - у + 4 = 0
- у² + 7 = 0
у² - 7 = 0
у² = 7
у = +- √7
Ответ: +-√7
у - 1 - (у² - 4) = у - 4
у - 1 - у² + 4 - у + 4 = 0
- у² + 7 = 0
у² - 7 = 0
у² = 7
у = +- √7
Ответ: +-√7
Похожие вопросы
Предмет: Биология,
автор: vk300709
Предмет: Українська мова,
автор: 29danya
Предмет: Математика,
автор: tenmariya0059
Предмет: Математика,
автор: Muxtar11